YangXue QingNao Wan, a Compound Chinese Medicine, Attenuates Cerebrovascular Hyperpermeability and Neuron Injury in Spontaneously Hypertensive Rat: Effect and Mechanism - Jiao, Ying-Qian; Huang, Ping; Yan, Li; Sun, Kai; Pan, Chun-Shui; Li, Quan; Fan, Jing-Yu; Ma, Zhi-Zhong; Han, Jing-Yan (Frontiers in Physiology, 2019)
Abstract Objective: The purpose of the study was to explore the effect of YangXue QingNao Wan (YXQNW), a compound Chinese medicine, on cerebral venule exudation, neuronal injury and related mechanisms in Spontaneously Hypertensive Rat (SHR). Methods: Fourteen week-old male spontaneously hypertensive rats (SHR) were used with Wister Kyoto (WKY) rats as control. YangXue QingNao Wan (YXQNW, 0.5 g/kg/day), enalapril (EN, 8 mg/kg/day), and NF (nifedipine, 7.1 mg/kg/day) were administrated orally for 4 weeks. To assess the effects of theYXQNW on blood presure, The systolic blood pressure (SBP), diastolic blood pressure (DBP), mean pressure (MBP), were measured were measured. After administering of the drugs for 4 weeks, the cerebral blood flow (CBF), albumin leakage in middle cerebral artery (MCA) area, the number and morphology of microvessels were assessed in hippocampus area and cortex. Neuronal damage and apoptosis were acesessed by Nissl staining and TUNEL staining. To assess the mechanisms of cerebrovascular hyperpermeability, we performed immunofluorescence and western blot to acsess the expression and integrity of cerebral microvascular tight junction (TJ) and caveolin-1 (Cav-1) in cortex. Energy metabolism and Src-MLC-MLCK pathway in cortex were assessed then for the futher mechanism. Results: SHR exhibited Evans blue extravasation, albumin leakage, increased brain water content, decreased cerebral blood flow, perivascular edema and neuronal apoptosis in hippocampus and cortex, all of which were attenuated by YXQNW treatment. YXQNW inhibited the downregulation of TJ proteins, mitochondrial Complex I, Complex II, and Complex V, and upregulation of caveolin-1, inhibiting Src/MLCK/MLC signaling in SHR. YXQNW combined with EN + NF revealed a better effect for some outcomes as compared with either YXQNW or EN + NF alone. Conclusion: Overall result shows the potential of YXQNW to attenuate BBB breakdown in SHR, which involves regulation of energy metabolism and Src/MLCK/MLC signaling. This result provides evidence supporting application of YXQNW as an adjuvant management for hypertension patients to prevent hypertensive encephalopathy.